INCONSISTENCY OF PHARMACEUTICAL PERSONNEL LICENSE REGULATION IN GOVERNMENT REGULATION NUMBER 51 YEAR 2009 CONCERNING PHARMACEUTICAL WORK - Said Ismala Kisma (STIH Putri Maharaja, 2022)
The issuance of Government Regulation Number 51 of 2009 concerning Pharmaceutical Work has the aim of encouraging social change to become a better direction through legal certainty. This normative legal research method examines the law from an internal perspective with the object of research being legal norms. The purpose of this research is to analyze the regulation of pharmacy staff licenses in Government Regulation No. 51 of 2009 concerning Pharmaceutical Work and to analyze the ideal setting of pharmaceutical staff in positive law. The results of the study explain that the regulation of permits for pharmaceutical workers in Government Regulation Number 51 of 2009 concerning Pharmaceutical Work can refer to Article 1 paragraph 22 or 52 paragraph (2) letter a of Government Regulation Number 51 of 2009 concerning Pharmaceutical Work. There is an inconsistency in the arrangement due to the content of the material being regulated contradicting each other. Ideally the Regulation of Pharmaceutical Workers in Positive Law, that Government Regulation Number 51 of 2009 concerning Pharmaceutical Work, nomenclature is not in accordance with the nomenclature stipulated in Law Number 36 of 2009 concerning Health, especially between the phrase work and practice.